HUBUNGAN SIFAT PEMESINAN DENGAN BERAT JENIS DAN JUMLAH PORI EMPAT JENIS KAYU KURANG DIKENAL ASAL KALIMANTAN TIMUR - Achmad Supriadi; Osly Rachman (Pusat Penelitian dan Pengembangan Hasil Hutan, 2003)
Machining properties of four lesser known wood species originated from natural forest in East Kalimantan were studied. The relationship between machining defects and specific gravity and amount of vessel was also analyzed. The machining operations were planing, shaping, boring, turning and sanding.The result revealed that machining properties were significantly affected by wood species. The machining qualities of lansat hutan (Lansium sp.), telisai (Planchonia grandis Ridl.) and rambai punai (Glochidion philippicum Robins.) woods with respect to criteria were good lo very good, while those nyaling (Mastixia trichomata Bl.) fair to very good. Either specific gravity or number of vessel was significantly related with the machinability 's defect- free values. Higher specific gravity tended the higher the machining qualities. Conversely, greater number of vessels brought about the lowering of machining properties.